Brief Report: Are Serious Falls Associated With Subsequent Fragility Fractures Among Veterans Living With HIV?. (1st October 2021) - Womack, Julie A.; Murphy, Terrence E.; Ramsey, Christine; Bathulapalli, Harini; Leo-Summers, Linda; Smith, Alexandria C.; Bates, Jonathan; Jarad, Samah; Gill, Thomas M.; Hsieh, Evelyn; Rodriguez-Barradas, Maria C.; Tien, Phyllis C.; et al.
Abstract : Background: The extensive research on falls and fragility fractures among persons living with HIV (PWH) has not explored the association between serious falls and subsequent fragility fracture. We explored this association. Setting: Veterans Aging Cohort Study. Methods: This analysis included 304, 951 6-month person- intervals over a 15-year period (2001–2015) contributed by 26, 373 PWH who were 50+ years of age (mean age 55 years) and taking antiretroviral therapy (ART). Serious falls (those falls significant enough to result in a visit to a health care provider) were identified by the external cause of injury codes and a machine learning algorithm applied to radiology reports. Fragility fractures were identified using ICD9 codes and included hip fracture, vertebral fractures, and upper arm fracture and were modeled with multivariable logistic regression with generalized estimating equations. Results: After adjustment, serious falls in the previous year were associated with increased risk of fragility fracture [odds ratio (OR) 2.10; 95% confidence interval (CI): 1.83 to 2.41]. The use of integrase inhibitors was the only ART risk factor (OR 1.17; 95% CI: 1.03 to 1.33). Other risk factors included the diagnosis of alcohol use disorder (OR 1.49; 95% CI: 1.31 to 1.70) and having a prescription for an opioid in the previous 6 months (OR 1.40; 95% CI: 1.27 to 1.53). Conclusions: Serious falls within the past year are strongly associated with fragility fractures among PWH on ART—largely a middle-aged population—much as they are among older adults in the general population.